TeV blazars: Status of observations - Krennrich, F; Biller, S; Bond, I; Boyle, P; Bradbury, S; Breslin, A; Buckley, J; Burdett, A; Gordo, J; Carter-Lewis, D; Catanese, M; Cawley, M; et al. (1999)
The close relation between ground-based TeV observations and satellite borne gamma-ray measurements has been important for the understanding of blazars. The observations which involve the TeV component in blazar studies are reviewed.